Variation Symmetry around Nd3+ Ion Saturated Solution of Medicinal Compounds with Reference to Judd-Ofelt Electronic Spectral Parameter - Aryamitra Pandey, Mr.; Tater, P.C.; Soni, K.P.; Joshi, G.K. (Asian Journal of Chemistry, 2010)
The stereo-environment of doped Nd3+ ion in various saturated solutions of some medicinal compounds has been studied for various electronic spectral parameters. The various electronic parameters, viz., Slater-Condon (Fk), Lande parameter (ζ4f), intensity of hypersensitive band (4G5/2), bonding parameter (b1/2), Judd-Ofelt parameter (Tλ) and Racah parameter (Ek) for Nd3+ ion doped in saturated solution of thiabendazole, piperazine, mebendazole, pyrantel pamoate and albendazole have been studied.